The Real Effects of PCAOB Inspection Reports on the M&A Deals of Non-Big 4 Accounting Firms - Lennox, Clive; Wu, Xi (The Accounting Review, 2024)
ABSTRACT Mergers and acquisitions (M&As) are an important way for non-Big 4 accounting firms to grow their businesses. Non-Big 4 firms also account for the vast majority of PCAOB inspections. Consistent with negative inspection reports signaling low quality at inspected firms, we find that non-Big 4 accounting firms conduct fewer M&A deals after they receive negative inspection reports. Additional analyses support our hypothesized signaling mechanism: (1) the chilling effect of inspection reports on M&A activity is stronger when the inspected firm’s business is focused on public company audits, (2) the effect is stronger when stakeholders at the target firm know less about the acquirer because the acquirer is located in a different city, and (3) clients at the target firm switch to new firms rather than move over to the acquirer if the acquirer received a negative inspection report prior to the M&A date. JEL Classifications: D82; G34; G38; M42; M48.